PROSPECTS OF THE XENON ANESTHESIA IN PEDIATRIC SURGERY - V.G. Bagaev; V.G. Amcheslavskii; D.I. Leonov (Педиатрическая фармакология)
Effective and safe anesthesia is the especially important problem in pediatric anesthesiology. The authors present data on the relatively new drug — xenon. Results of the investigations of both foreign and Russian scientists are cited. The mechanism of action of xenon and its effect on systemic and cerebral circulation and central nervous system, hemostasis, and other systems are demonstrated. The authors pay special attention to the factors responsible for the restricted use of the gas in general practice, indicate the peculiarities of its use in pediatric practice.Key words: xenon, the mechanism of action, anesthesia, advantages, disadvantages, impact on the body, children.